ANALYSIS OF FACTORS AFFECTING INCREASING TEACHER PERFORMANCE THROUGH MANAGEMENT PRINCIPAL COMMUNICATIONS - Samiyah (Progresif : Media Publikasi Ilmiah, 2024)
Education plays a central role in the development of a nation, and high-quality education is expected to produce future generations capable of competing on the international stage. Improving the quality of education in Indonesia involves supportive factors, where the role of the school principal as a leader and teachers as educators is crucial. Enhancing the performance of teachers, as a key element in the educational process, requires effective communication management between the school principal and teachers. This research aims to analyze and elucidate the factors influencing teacher performance and how the communication management of the school principal plays a crucial role in improving teacher performance. The research methodology employed is normative through literature review. The data analysis techniques used are descriptive and argumentative. Based on the research, it is found that factors affecting teacher performance involve effectiveness and efficiency, authority and responsibility, discipline, initiative, skills and expertise, knowledge, work design, personality, motivation, leadership, leadership style, organizational culture, job satisfaction, and working environment. Furthermore, the role of communication management by the school principal in enhancing teacher performance is essential. The school principal, as a leader, must be able to create a positive work environment, support the professional growth of teachers, and encourage better performance. Open, clear, and sustainable communication is the key to establishing a harmonious working relationship in the educational environment